3p+24q+42=

Simple and best practice solution for 3p+24q+42= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3p+24q+42= equation:


Simplifying
3p + 24q + 42 = 0

Reorder the terms:
42 + 3p + 24q = 0

Solving
42 + 3p + 24q = 0

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-42' to each side of the equation.
42 + 3p + -42 + 24q = 0 + -42

Reorder the terms:
42 + -42 + 3p + 24q = 0 + -42

Combine like terms: 42 + -42 = 0
0 + 3p + 24q = 0 + -42
3p + 24q = 0 + -42

Combine like terms: 0 + -42 = -42
3p + 24q = -42

Add '-24q' to each side of the equation.
3p + 24q + -24q = -42 + -24q

Combine like terms: 24q + -24q = 0
3p + 0 = -42 + -24q
3p = -42 + -24q

Divide each side by '3'.
p = -14 + -8q

Simplifying
p = -14 + -8q

See similar equations:

| 13(x-2)-2x=7 | | 191-2x=34x+23 | | 5n-2=n+5 | | 8x-4x+2x-6x= | | -6x=2y+12 | | 4x^2+33x=-54 | | 8x-4x+(4x-8)/2-4x/3-6x+4=x+2-16 | | -log(x)=1.5 | | 4(x-9)=4 | | 85-3X=10+20 | | x=5.33 | | (2x^2)-11x+12=0 | | 2X-2=9X-29 | | (x+4)(x+6)+8=x(x+1)-13 | | 17x^2-46x+14=81 | | 0=3k^2+2k-40 | | (-3x+1)-(-3x+1)+12x=-3 | | (-3x+1)-(-3x+1)=+12x | | 3x+8=5x-6(x-4) | | 4x-x+5=20 | | (-3x+1)=-(-3x+1)+12x | | 7+5x-1=21 | | 5-5=12x-89 | | 5x+37=59-13x | | 35-5x=4x+16 | | 59-13x=37+5x | | 84+4x=7x | | x^5-21x+1=0 | | 8x+8=5x+28 | | .875x-2=.6 | | 6x-19=49 | | .875x-2=.66666666666666666666 |

Equations solver categories